Editorial - Adendorff, Susan (The South African Journal of Industrial Engineering, 2012)
As the 25th year of the existence of the South African Journal of Industrial Engineering (SAJIE) draws to a close, a new day has dawned for the Journal. The Journal has become an on-line, open-access publication accessible at http://sajie.journals.ac.za/pub/index. During the course of 2012, all issues from 1987 to the present were uploaded onto the new website, creating a full archive of all articles ever published in SAJIE since 1987. Previously only editions from the last few years were available electronically to subscribers to specific web services. It is hoped that this will increase the visibility of the Journal and bolster the impact factor of SAJIE even further.